Steroid‐sparing maintenance immunosuppression is safe and effective after simultaneous liver‐kidney transplantation. Issue 10 (2nd August 2020) - Weeks, Sharon R.; Luo, Xun; Toman, Lindsey; Gurakar, Ahmet O.; Naqvi, Fizza F.; Alqahtani, Saleh A.; Philosophe, Benjamin; Cameron, Andrew M.; Desai, Niraj M.; Ottmann, Shane E.; Segev, Dorry L.; Garonzik‐Wang, Jacqueline
Abstract: Optimization of maintenance immunosuppression (mIS) regimens in the transplant recipient requires a balance between sufficient potency to prevent rejection and avoidance of excessive immunosuppression to prevent toxicities and complications. The optimal regimen after simultaneous liver‐kidney (SLK) transplantation remains unclear, but small single‐center reports have shown success with steroid‐sparing regimens. We studied 4184 adult SLK recipients using the Scientific Registry of Transplant Recipients, from March 1, 2002, to February 28, 2017, on tacrolimus‐based regimens at 1 year post‐transplant. We determined the association between mIS regimen and mortality and graft failure using Cox proportional hazard models. The use of steroid‐sparing regimens increased post‐transplant, from 16.1% at discharge to 88.0% at 5 years. Using multi‐level logistic regression modeling, we found center‐level variation to be the major contributor to choice of mIS regimen (ICC 44.5%; 95% CI: 36.2%‐53.0%). In multivariate analysis, use of a steroid‐sparing regimen at 1 year was associated with a 21% decreased risk of mortality compared to steroid‐containing regimens (aHR 0.79, P = .01) and 20% decreased risk of liver graft failure (aHR 0.80, P = .01), without differences in kidney graft loss risk (aHR 0.92, P = .6). Among SLK recipients, the use of a steroid‐sparing regimen appears to be safe and effective without adverse effects on patient or graft survival.